From Mendel's discovery on pea to today's plant genetics and breeding : Commemorating the 150th anniversary of the reading of Mendel's discovery - Smýkal, Petr; K Varshney, Rajeev; K Singh, Vikas; Coyne, Clarice J; Domoney, Claire; Kejnovský, Eduard; Warkentin, Thomas (TAG. Theoretical and applied genetics. Theoretische und angewandte Genetik, 2016)
This work discusses several selected topics of plant genetics and breeding in relation to the 150th anniversary of the seminal work of Gregor Johann Mendel. In 2015, we celebrated the 150th anniversary of the presentation of the seminal work of Gregor Johann Mendel. While Darwin's theory of evolution was based on differential survival and differential reproductive success, Mendel's theory of heredity relies on equality and stability throughout all stages of the life cycle. Darwin's concepts were continuous variation and "soft" heredity; Mendel espoused discontinuous variation and "hard" heredity. Thus, the combination of Mendelian genetics with Darwin's theory of natural selection was the process that resulted in the modern synthesis of evolutionary biology. Although biology, genetics, and genomics have been revolutionized in recent years, modern genetics will forever rely on simple principles founded on pea breeding using seven single gene characters. Purposeful use of mutants to study gene function is one of the essential tools of modern genetics. Today, over 100 plant species genomes have been sequenced. Mapping populations and their use in segregation of molecular markers and marker-trait association to map and isolate genes, were developed on the basis of Mendel's work. Genome-wide or genomic selection is a recent approach for the development of improved breeding lines. The analysis of complex traits has been enhanced by high-throughput phenotyping and developments in statistical and modeling methods for the analysis of phenotypic data. Introgression of novel alleles from landraces and wild relatives widens genetic diversity and improves traits; transgenic methodologies allow for the introduction of novel genes from diverse sources, and gene editing approaches offer possibilities to manipulate gene in a precise manner.
Keywords: hrách setý; šlechtění rostlin; mapování chromozomů; Genetics; dějiny 19. století; selekce (genetika); Pisum sativum; History, 19th Century; fenotyp; Phenotype; dějiny 21. století; genetická variace; dějiny 20. století; Selection, Genetic; genomika; geneticky modifikované rostliny; Plants, Genetically Modified; genetika; lokus kvantitativního znaku; Quantitative Trait Loci; Chromosome Mapping; History, 20th Century; History, 21st Century; genom rostlinný; Genome, Plant; Plant Breeding; Genetic Variation; Genomics